O armário de Deus no armário dos homens : alternativas teológicas para o acolhimento e livre expressão da pessoa homossexual na comunidade cristã brasileira e contemporaneidade - Câmara, Uipirangi Franklin da Silva (2008)
This thesis combines an analysis of elements of the critical-historical method with the social historical view. It emphasizes a discourse analysis to present theological alternatives which enable homosexual persons to express fully and freely their spirituality in Brazilian Christian communities. The presented research gives an overview of homosexuality in Brazil, showing different aspects, values and movements. A leading question is the homosexual identity, often seen as a perversion, an abnormality, a crime or disease, with consequently a stigma of marginalization and exclusion. Also, the proposed research presents an alternative identity in the search of rights of homosexuals as citizens, both theoretically as well as from a political point of view. We will show in which ways Christianity in Brazil, from a Catholic and Protestant theological perspective, understands homosexuality, including the arguments, teachings and principal postures. From such an analysis, we will identify some theologically viable and legitimate alternatives that enable the homosexual person to express oneself freely in the Christian communities. We will critically analyze gender construction, in its binary reference as masculine / feminine; and deconstruct it because it is detrimental to the understanding of multiplicity and complexity of social identities. In addition and as an extension of this project a necessary deconstruction of “God talk” as presently a masculine characterization needs to be undertaken. (AU)